Incorporating MXene into Boron Nitride/Poly(Vinyl Alcohol) Composite Films to Enhance Thermal and Mechanical Properties - Lee, Seonmin (Polymers (Basel), 2021)
Aggregated boron nitride (ABN) is advantageous for increasing the packing and thermal conductivity of the matrix in composite materials, but can deteriorate the mechanical properties by breaking during processing. In addition, there are few studies on the use of Ti(3)C(2) MXene as thermally conductive fillers. Herein, the development of a novel composite film is described. It incorporates MXene and ABN into poly(vinyl alcohol) (PVA) to achieve a high thermal conductivity. Polysilazane (PSZ)-coated ABN formed a heat conduction path in the composite film, and MXene supported it to further improve the thermal conductivity. The prepared polymer composite film is shown to provide through-plane and in-plane thermal conductivities of 1.51 and 4.28 W/mK at total filler contents of 44 wt.%. The composite film is also shown to exhibit a tensile strength of 11.96 MPa, which is much greater than that without MXene. Thus, it demonstrates that incorporating MXene as a thermally conductive filler can enhance the thermal and mechanical properties of composite films.